Pulse assessment is important with blood pressure measurement in individuals with continuous flow left ventricular assist devices. Issue 2 (February 2021) - Marcos-Abdala, Hernan G; Cruz-Solbes, Ana S; Hussain, Imad; Trachtenberg, Barry; Ashrith, Guha; Torre-Amione, Guillermo; Bruckner, Brian; Suarez, Erik E; Estep, Jerry D; Bhimaraj, Arvind
While Doppler and cuff blood pressure techniques are prevalent methods of assessing blood pressure in patients with continuous flow left ventricular assist devices, the impact of pulsatility on measurement is not well established. Retrospective chart analysis of clinical variables including pulse perception, blood pressure (Doppler and standard cuff), and aortic valve opening on echo at clinic visit were abstracted. Stable outpatients on continuous flow left ventricular assist devices support with concomitant portable echo assessment were included. Mean average difference was calculated and Pearson's correlation performed for all those patients who had both Doppler and cuff pressure obtained. In all, 74 Heartmate-II patients with a median time from implant of 380 days were analyzed. A pulse was perceived in 82% of patients with persistent aortic valve opening on portable echo and also in 30% of those who had a persistently closed aortic valve. The mean average difference between the Doppler and systolic cuff pressure was ~13 mmHg ( r  = 0.5, p  = 0.004) when a pulse was present and ~11 mmHg when aortic valve was open ( r  = 0.68, p  < 0.0001). Pulse presence seems to reflect aortic valve opening a majority of the time but not always. In the presence of a prominent pulse or persistent aortic valve opening, the Doppler pressure seems to be more reflective of a systolic pressure than mean perfusion pressure. Hence, assessment of pulsatility needs to be incorporated into blood pressure measurement methods for patients with continuous flow left ventricular assist devices.